2020
DOI: 10.9734/ajarr/2020/v9i430226
|View full text |Cite
|
Sign up to set email alerts
|

Study on Radiation Interception and Use in Some Mustard Varieties

Abstract: Aim: Solar radiation is the unique source of energy which drives the photosynthesis of green plants for producing biomass to living being. Use efficiency of solar radiation to produce biomass has been quantified for many crops in field condition but no study is undertaken for mustard although it is an important oil seed crop in the world as well as in Bangladesh. Therefore, the present study was undertaken to evaluate the radiation-use efficiency of mustard crop. Study Design: The experiment was laid out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Mehrotra et al [26] observed a 16-69 percent increase in mustard seed yield due to boron application. Overall, the seed yield of mustard in this study was found similar as those reported earlier [20,[25][26][27][28][29][30][31][32]. The yield components and seed yield of mustard as affected by the application of different levels of sulphur and boron in this study are also supported by Rahman [16], Hossain et al [33] and Biswas [34].…”
Section: Yield and Yield Componentssupporting
confidence: 89%
“…Mehrotra et al [26] observed a 16-69 percent increase in mustard seed yield due to boron application. Overall, the seed yield of mustard in this study was found similar as those reported earlier [20,[25][26][27][28][29][30][31][32]. The yield components and seed yield of mustard as affected by the application of different levels of sulphur and boron in this study are also supported by Rahman [16], Hossain et al [33] and Biswas [34].…”
Section: Yield and Yield Componentssupporting
confidence: 89%
“…Rana et al [34] reported that at 90% pod formation period, plant GDD, HTU and PTU requirements decreased with delay in sowing on different days. More GDD is required in early sowing to reach physiological maturity compared to late sowing and this may be owing to high temperatures during the late growing season, which forced the crop to mature [35][36][37].…”
Section: Discussionmentioning
confidence: 99%